Foundations of Change: How the 10th Century BCE Sparked the Second International Age - Banyai , Michael (Antiguo Oriente, 2025)
The paper highlights the mid-10th century BCE as a pivotal era in the ancient Near East. This period is identified as the beginning of a second international age, following approximately two centuries of economic stagnation beginning with the end of the Late Bronze Age. Israel’s unique strategic position between the Red Sea and the Mediterranean, also providing a land bridge between Africa and Asia, as well as its contiguity with Phoenicia, the last surviving Mediterranean naval power, offered 10th century Israel an incomparable geopolitical advantage as soon as it was ready to make use of it. There is an urgent need to re-evaluate the activity attributed to Solomon at Ezion-Geber following the revelation of large quantities of slag-tempered Negevite Wares in Pratico’s technical investigation of the pottery at Ezion-Geber / Tell el-Kheleifeh. This type of Negevite Wares casually dated to the Iron IIA period prompts a discussion concerning the appropriate chronological position of Tell el-Kheleifeh and its relation to the Ezion-Geber narratives implicating King Solomon. The inscription ALEPPO 7, attributed to Taita I, King of Palasatini, reveals the existence of a thriving international horse trade between Egypt and Palasatini. Based on the historical context of the inscription and supporting radiocarbon evidence, Taita I must be dated to the 10th century BCE. The fact that this trade would have traversed Israel during this period highlights the role ascribed to Solomon in the biblical narrative, where he is credited with facilitating a horse trade between Egypt and the neo-Hittite states. The Mediterranean expeditions of the Phoenicians, dated by recent research to the Iron Age IIA, the period of the United Monarchy, prompt the question of its participation in these Phoenician ventures. Siamun, the pharaoh most likely at the helm when these commercial enterprises began, serves as the key chronological anchor, effectively linking the archaeological findings from the mid-10th century to the broader political context of that era.